Does learning you are autistic at a younger age lead to better adult outcomes? A participatory exploration of the perspectives of autistic university students. (January 2023) - Oredipe, Tomisin; Kofner, Bella; Riccio, Ariana; Cage, Eilidh; Vincent, Jonathan; Kapp, Steven K; Dwyer, Patrick; Gillespie-Lynch, Kristen
Many autistic people do not learn they are autistic until adulthood. Parents may wait to tell a child they are autistic until they feel the child is "ready." In this study, a participatory team of autistic and non-autistic researchers examined whether learning one is autistic at a younger age is associated with heightened well-being and Autism-Specific Quality of Life among autistic university students. Autistic students ( n = 78) completed an online survey. They shared when and how they learned they were autistic, how they felt about autism when first learning they are autistic and now, and when they would tell autistic children about their autism. Learning one is autistic earlier was associated with heightened quality of life and well-being in adulthood. However, learning one is autistic at an older age was associated with more positive emotions about autism when first learning one is autistic. Participants expressed both positive and negative emotions about autism and highlighted contextual factors to consider when telling a child about autism. Findings suggest that telling a child that they are autistic at a younger age empowers them by providing access to support and a foundation for self-understanding that helps them thrive in adulthood. Lay abstract: People learn they are autistic at different ages. We wanted to know if telling kids they are autistic earlier helps them feel better about their lives when they grow up. We are a team of autistic and non-autistic students and professors. Seventy-eight autistic university students did our online survey. They shared how they found out they were autistic and how they felt about being autistic. They also shared how they feel about their lives now. Around the same number of students learned they were autistic from doctors and parents. Students who learned they were autistic when they were younger felt happier about their lives than people who learned they were autistic when they were older. Students who learned they were autistic when they were older felt happier about being autistic when they first found out than people who did not have to wait as long. Our study shows that it is probably best to tell people they are autistic as soon as possible. The students who did our study did not think it was a good idea to wait until children are adults to tell them they are autistic. They said that parents should tell their children they are autistic in ways that help them understand and feel good about who they are.